Are you experienced? - Sonnenblick, Jordan (New York : Feiwel and Friends, 2013)
When his girlfriend asks him to perform at a protest rally, Rich jumps at the chance. Unfortunately, the police show up, and Rich is in big trouble. Again. To make matters worse, it's near the anniversary of his uncle's death from a drug overdose years ago, which makes Rich's dad depressed. Frustrated by his dad's silence, Rich breaks into a locked cabinet that holds a prized possession: an electric guitar signed by Jimi Hendrix. Before he knows it, Rich is transported to the side of a road, it's 1969, and he's at Woodstock. When he meets his fifteen-year-old dad and his uncle, what Rich learns, who he meets, and what he does could change his life forever.
Keywords: Time travel -- Juvenile fiction; Time travel -- Fiction; Fantasy; Fantasy fiction; Young adult fiction